Training and Work Environment on Employee Performance: Mediating Effect of Work Motivation in State-Owned Hospital Holdings - Irawati Winarno; Asep Saifudin; Deni Gustiawan; Winaya Puwanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The healthcare industry faces increasing challenges in improving service quality, patient safety, and operational efficiency, requiring optimal employee performance. However, issues such as competency gaps, less conducive work environments, and uneven work motivation hinder performance improvement. This study examines the influence of training and work environment on employee performance, with work motivation as a mediating variable. Partial Least Squares Structural Equation Modeling (SEM-PLS) was used as a quantitative explanatory method. Likert-scale questionnaires were used to collect data, and SmartPLS was used for analysis. A total of 222 respondents were chosen by simple random sampling. The results indicate that training and the work environment have significant effects on employee performance. Both training and work environment significantly influence work motivation. Work motivation shows the strongest effect on performance and partially mediates the relationships between training and work environment on performance. The study highlights the critical role of work motivation in enhancing employee performance, supported by effective training and a conducive work environment. These findings provide practical guidance for improving human resource management strategies in healthcare organizations.